2017
DOI: 10.18632/oncotarget.20234
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosylmethionine and methylthioadenosine inhibit cancer metastasis by targeting microRNA 34a/b-methionine adenosyltransferase 2A/2B axis

Abstract: MicroRNA-34a (miR-34a) is down-regulated in colorectal cancers (CRC) and required for interleukin-6 (IL-6)-induced CRC metastasis. Mice lacking miR-34a developed more invasive cancer in a colitis-associated cancer model. In the same model, S-adenosylmethionine (SAMe) and methylthioadenosine (MTA) inhibited IL-6/STAT3 and lowered tumor burden. SAMe and MTA reduce the expression of methionine adenosyltransferase 2A (MAT2A) and there are consensus binding sites for miR-34a/b in the MAT2A 3’UTR. Here we examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 30 publications
5
37
0
Order By: Relevance
“…In a chemically induced hepatocarcinogenesis rat model, both endogenous and exogenous MTA levels were found to be negatively correlated with preneoplastic liver lesions and DNA synthesis 27, 29. Similar inhibitory effects of MTA have also been observed in cultured HCT116 human colon cancer cells, colorectal cancer cells, HeLa cervical cancer cells, Daudi and Raji lymphoma cells, erythroleukemia cells, promyelocytic cells and mitogen stimulated human peripheral blood lymphocytes 8, 31-35.…”
Section: Mta and Tumorsupporting
confidence: 72%
See 1 more Smart Citation
“…In a chemically induced hepatocarcinogenesis rat model, both endogenous and exogenous MTA levels were found to be negatively correlated with preneoplastic liver lesions and DNA synthesis 27, 29. Similar inhibitory effects of MTA have also been observed in cultured HCT116 human colon cancer cells, colorectal cancer cells, HeLa cervical cancer cells, Daudi and Raji lymphoma cells, erythroleukemia cells, promyelocytic cells and mitogen stimulated human peripheral blood lymphocytes 8, 31-35.…”
Section: Mta and Tumorsupporting
confidence: 72%
“…It is noteworthy that most of these studies indicate that MTA had the opposite effect on the apoptosis of normal versus cancerous cells. In vitro , it enhances the apoptosis of human RKO and SW620 colon cancer cells 35, 41 and of HuH7 liver cancer cells 42. However, it does not have such effects on normal colon epithelial cells or even has anti-apoptotic effects on normal hepatocytes 41, 42.…”
Section: Mta and Tumormentioning
confidence: 99%
“…These discrepancies might be due to the different cellular context and tumor types and remain to be elucidated. Interestingly, while this article was in preparation, Tomasi et al reported that overexpression of MAT2A promoted ERK activation and cell migration in prostate and pancreatic cancer cells which do not express MAT1A. Taken our and Tomasi's data together, it is suggested that the liver‐specific MAT1A may play a critical role in metastasis of liver cancer and both increasing MAT2A and decreasing MAT1A are necessary for HCC metastasis.…”
Section: Discussionmentioning
confidence: 56%
“…Over-expression of miR-34a or miR-34b lead to the low expression level of MAT2B, mainly in the protein expression level of CWR22Rv-1 and MIA PaCa-2 cells [ 65 ]. Using microRNA microarray, Lo TF et al [ 66 ] found that after berberine treatment, the expression of miR-21-3p (previously named miR-21) up-regulated in HepG2 human hepatoma cell line.…”
Section: Discussionmentioning
confidence: 99%